2008
DOI: 10.1007/s00256-008-0518-4
|View full text |Cite
|
Sign up to set email alerts
|

Angioleiomyoma: magnetic resonance imaging features in ten cases

Abstract: This is the largest reported MRI series of extremity musculoskeletal angioleiomyoma. Angioleiomyoma should be considered in the differential diagnosis of a superficial mass in the hand or foot, particularly when characteristic linear or branching hyperintensity is seen on T2W or STIR images.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
3
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 6 publications
4
45
3
1
Order By: Relevance
“…On MRI, the lesion has been described as isointense to skeletal muscle on T1-weighted images and homogenous to heterogeneously hyperintense on T2-weighted sequences. The characteristic features described for angiomyomas include: a hypointense peripheral capsule with linear or branching internal hyperintensities on T2-weighted images and postcontrast diffuse homogenous enhancement, with one study describing a vessel leading up to the lesion in a majority of cases, as also seen in our case 3 8 9…”
Section: Discussionmentioning
confidence: 59%
“…On MRI, the lesion has been described as isointense to skeletal muscle on T1-weighted images and homogenous to heterogeneously hyperintense on T2-weighted sequences. The characteristic features described for angiomyomas include: a hypointense peripheral capsule with linear or branching internal hyperintensities on T2-weighted images and postcontrast diffuse homogenous enhancement, with one study describing a vessel leading up to the lesion in a majority of cases, as also seen in our case 3 8 9…”
Section: Discussionmentioning
confidence: 59%
“…Cellular leiomyomas show relatively higher signal intensity on T2-weighted series and contrast enhancement following injection of contrast material intravenously (7). Similar to cellular leiomyomas, vascular leiomyomas also show hyperintense signal intensity on T2-weigthed series and contrast enhancement (8, 9). Degenerated leiomyomas have variable appearances on T2-weighted images and contrast-enhanced examination.…”
Section: Discussionmentioning
confidence: 93%
“…Hwang et al [11] reported that hyperintense areas on T2-weighted images corresponded with the presence of numerous vessels and smooth muscle, while areas isointense to skeletal muscle indicated tough fibrous tissue. Gupte [12]discussed ten cases of angioleiomyoma and found that typical lesions appeared homogeneous and were isointense to skeletal muscle on T1-weighted spin echo (SE) images. On T2-weighted fast spin echo (FSE), fat-saturated (FS), and short tau inversion recovery (STIR) images, the lesion was isointense to the surrounding fat and had an internal hyperintense area that was linear or branching in shape.…”
Section: Discussionmentioning
confidence: 99%